The Crisis of the Political. Polis and an Individual - Kazlauskas, Raimondas (Sociologija. Mintis ir veiksmas, 2022)
The article discusses the crisis of the political, treating this phenomenon as an interactive constellation of political, over-political and apolitical factors. The aim is to reconstruct the assumptions of the crisis and highlight its main features in the context of ancient Greece. Under the influence of Dionysian religion, theater was established as a compelling and universally accessible authority to legitimize democracy. Therefore my analysis focuses on the social change after which democracy was no longer perceived as a form of governance but as a form of collective ownership. The article explains how the unbridled demonstration of power quickly erased the long-cherished principle of verbal argumentation and pushed Greeks to practice of power politics. It is shown how, with the establishment of autocracy, parallel interchange between political and anti-political institutions emerged in the Greek polis.